Preparation and evaluation of a chitosan-coated antioxidant liposome containing vitamin C and folic acid - Jiao, Zhen; Wang, Xiudong; Yin, Yuting; Xia, Jingxin; Mei, Yanan (Journal of microencapsulation, 2018)
Vitamin C (VC) and folic acid (FA) are the important nutrient and antioxidant in human body. In order to improve their stability, their co-loaded liposomes (VCFA-Lip) and chitosan-coated liposomes (CS-VCFA-Lip) are prepared and characterised. The mean particle size of VCFA-Lip and CS-VCFA-Lip is 138 nm and 249 nm, respectively. The encapsulation efficiencies of both drugs for CS-VCFA-Lip are much higher than those for VCFA-Lip. Furthermore, the experimental results show that the antioxidant activity of CS-VCFA-Lip is higher than that of VCFA-Lip. Moreover, the storage stability study reveals that the chitosan coating can efficiently improve the physical stability of VCFA-Lip. These results indicate that stability of VC and FA can be greatly improved after being wrapped by liposomes. In addition, the performance of CS-VCFA-Lip is better than VCFA-Lip, indicating CS-VCFA-Lip can be applied as a promising delivery system for the antioxidant defence system to the food industry and cosmetic industry.